2020
DOI: 10.3389/fspas.2020.595929
|View full text |Cite
|
Sign up to set email alerts
|

A Mission Concept to Determine the Magnetospheric Causes of Aurora

Abstract: Insufficiently accurate magnetic-field-line mapping between the aurora and the equatorial magnetosphere prevents us from determining the cause of many types of aurora. An important example is the longstanding question of how the magnetosphere drives low-latitude (growth-phase) auroral arcs: a large number of diverse generator mechanisms have been hypothesized but equatorial magnetospheric measurements cannot be unambiguously connected to arcs in the ionosphere, preventing the community from identifying the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…This should significantly increase the uncertainty of any mappings, thus casting doubt on any attempt to probe the reconnection onset solely from ground‐based observations. More systematic investigations of conjunctions between ground‐based and equatorial signatures of current sheet thinning and dipolarization, supplemented by future experiments (see, e.g., Borovsky et al., 2020), are needed to establish ground‐based signatures of the pre‐onset substrom dynamics (see discussion in, e.g., Runov et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This should significantly increase the uncertainty of any mappings, thus casting doubt on any attempt to probe the reconnection onset solely from ground‐based observations. More systematic investigations of conjunctions between ground‐based and equatorial signatures of current sheet thinning and dipolarization, supplemented by future experiments (see, e.g., Borovsky et al., 2020), are needed to establish ground‐based signatures of the pre‐onset substrom dynamics (see discussion in, e.g., Runov et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…On the main spacecraft it is essential to accurately know the direction of the local magnetic field to be able to point the accelerator beam into the atmospheric loss cone. In actuality the northern and southern atmospheric loss cones for energetic electrons both are shifted eastward from the magnetic-field direction owing to finite-gyroradii effects in the TABLE 1 Summary of the science of MIO for the diverse Earth-systemscience communities: see also Sanchez et al, 2019, and Borovsky et al, 2020c The non-spinning mother spacecraft carrying the electron Accelerator. The green cone is the range of magnetic steering of the relativistic electron beam.…”
Section: The Magnetosphere-ionosphere Observatory Mission Overviewmentioning
confidence: 99%
“…Scientific observation can be achieved by actively emitting an electron beam into the space environment (Borovsky, Delzanno, Dors, et al., 2020; Borovsky, Delzanno, & Henderson, 2020), as proven by several electron beam sounding experiments conducted during the 1970s–1990s (Hendrickson et al., 1975; Hess et al., 1971; Matsumoto et al., 1975). Recent research has also shown that artificial electron beams can be used for studying beam‐plasma interaction physics, magnetosphere‐ionosphere coupling, and tracing magnetospheric field lines (Borovsky et al., 2022; Mishin, 2019; Rae et al., 2022; Reeves et al., 2020).…”
Section: Introductionmentioning
confidence: 99%